2023
DOI: 10.1002/slct.202300296
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antifungal Activity of Electrosprayed Poly (vinyl alcohol)/Chitosan Nanospheres Loaded with Sage Essential Oil on the Viability of Aspergillus niger and Botrytis cinerea

Abstract: In this study, sage essential oil (SEO) loaded nanoparticles were tested in terms of their antifungal properties. In this respect, the electrospray method was employed to fabricate SEOloaded nanoparticles (SNPs) by encapsulation of different concentrations (0.0, 0.25 %, 0.5 %, and 1 % v/v) of SEO within poly(vinyl alcohol)/chitosan-based nanoparticles (PVA/Chi NPs). The FTIR, DSC, and SEM analyses divulged that SEO could be successfully encapsulated within nanoparticles, possessing a spherical shape and high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The tested MIC value against B. cinerea was 0.35 μL/mL, surpassing the efficacy of Angelica archangelica EO (5.5 g/L) and sage EO reported by previous studies. , The antifungal activity of Poliomintha longiflora EO against B. cinerea and C.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The tested MIC value against B. cinerea was 0.35 μL/mL, surpassing the efficacy of Angelica archangelica EO (5.5 g/L) and sage EO reported by previous studies. , The antifungal activity of Poliomintha longiflora EO against B. cinerea and C.…”
Section: Resultsmentioning
confidence: 52%
“…82 The tested MIC value against B. cinerea was 0.35 μL/mL, surpassing the efficacy of Angelica archangelica EO (5.5 g/L) and sage EO reported by previous studies. 83,84 The antifungal activity of Poliomintha longiflora EO against B. cinerea and C. gloeosporioides has been confirmed, with MIC values of 0.8 and 1.0 g/L, respectively. 85 The inhibition of MEO on C. gloeosporioides was slightly worse than on B. cinerea, represented by an MIC of 0.45 and an IC 50 of 0.3193 μL/ mL, yet it outperformed the savory EO, which had an IC 50 of 0.5842 μL/mL reported by Sarkhosh et al 86 The fungitoxic function of peppermint EO was confirmed in which this substance drastically hindered the growth of mycelia at 100 μL/mL.…”
Section: Extraction and Antioxidant Activity Assay Of Heomentioning
confidence: 86%
“…Stapf [64]; Hyssopus officinalis L. [65]; Pistacia atlantica Desf. [66]; Salvia officinalis L. [67]; Thymus daenensis Celak. and Anethum graveolens L. [68]; Thymus vulgaris L. and Piper betel L. [69]; Zataria multiflora Boiss.…”
Section: Comparison With Other Nanocarriers Tested Against the Same P...mentioning
confidence: 99%